FACTORS THAT CAN AFFECT COMPANY PERFORMANCE BY MODERATING PROFITABILITY IN COMPANIES IN INDONESIA - Ermanto Hidayat; Harti Budi Yanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to analyze the influence of green accounting, corporate social responsibility, intellectual capital, and ownership structure on company performance through profitability. This study uses a sample taken of manufacturing companies listed on the Indonesia Stock Exchange (www.idx.co.id) for 2023 so that a final sample of 200 observation data is obtained. The data were analyzed using SPSS software with multiple regression analysis, descriptive analysis, classical assumption test and hypothesis. The results of the test conducted by the researcher can be concluded that green accounting and corporate responsibility have no effect on the company's performance. Meanwhile, intellectual capital and ownership structure have a significant positive effect on the company's performance and profitability cannot moderate green accounting on the company's performance. However, it is able to strengthen corporate responsibility, intellectual capital, and ownership structure for company performance.